PENYULUHAN MANFAAT PENANAMAN TANAMAN OBAT (TOGA) DI MASA PANDEMI DIDESA CIBIRU HILIR KECAMATAN CILEUNYI KABUPATEN BANDUNG - Ooy Siti Halimah; Nurul Noviyanti; Tania Aldyla; Nisa Aulia Dwiyanti; Silvia Alfi Nurfatwa; Giadi Fachrul Husaeri Dewia; Aldi Gilang Ramadhan; Zainal Abidin; Ayu Dharmayati (Universitas Al Ghifari, 2021)
The covid-19, is the thing that contains the emergence of various kinds of problems at this time. The economy, health and so on are affected by this covid-19 virus. Until now, the world has entered the Covid-19 pandemic, which requires everyone to follow standard health protocols in order to maintain health as a top priority. In response to the COVID-19 pandemic, a program from universities, carried out the student study service activities with the theme